Governance and sustainability : new challenges for states, companies and civil society - Petschow, Ulrich, 1952-; Rosenau, James N.; Weizsäcker, Ernst U. von (Ernst Ulrich), 1939- (Greenleaf Publishing, 2005)
Examines integrating the environmental, social and economic dimensions of sustainable development, within the framework of governance processes. This book covers the key actors, their agendas and methods, forms of organisation, problems and limits, and real-life examples of governance at the regional, national and international level.